PEMBATALAN PERJANJIAN SECARA SEPIHAK OLEH CALON JEMAAH UMROH SILVER SILK TOUR AND TRAVEL KARENA PANDEMI COVID-19 - Aldo Virgiansyah; Firdaus Firdaus; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Hajj and Umrah are obligatory acts of worship for every Muslim who can afford it. The agreement publishes an agreement between two people who are made. Implementation of the departure of prospective Hajj and Umrah pilgrims carried out by the Hajj and Umrah organizers using an agreement. The agreement made is binding on both parties, namely between the company or the organizing bureau as the first party and prospective Hajj and Umrah pilgrims as the second party. The cancellation of the agreement unilaterally cannot be carried out and must first fulfill the elements of being able to cancel an agreement. The purpose of writing this thesis, namely: First, to find out the form of implementation of the Umrah agreement due to the covid-19 pandemic, Second: to find out how Silver Silk Tour and Travel is responsible for the Umrah agreement party due to the covid-19 pandemic.used in this study using sociological research methods, namely research that wants to see the correlation between and society, so as to be able to reveal the effectiveness of law in society and identify unwritten laws that apply to society, while the sources of data are primary data, secondary data, and secondary data. tertiary, data collection in this study by interview and document study methods.From the results of the research problem, there are two main things that can guarantee, First, the challenge of a unilateral agreement made by prospective Silver Silk Tour and Travel Umrah pilgrims, the agreement between the prospective Silver Silk Tour and Travel Umrah pilgrims and the Silver Silk Tour and Travel does not meet the elements - elements for an agreement to be cancelled. Second: the problem of legal liability given by Silver Silk Tour and Travel to prospective Silver Silk Tour and Travel pilgrims who promise unilaterally that there is nothing to show that Silver Silk Tour and Travel must provide an accountability.Keywords: Cancellation - covid19 liability - covenant